O conceito de autoestima na análise do comportamento - Marcelino, Madeleine Reinert (2023)
This thesis consists of three studies that address the theme of self-esteem in Behavior Analysis. The first study is a systematic review of specific Behavior Analysis books and journals on self-esteem. Key findings include the scarcity of studies and the lack of a well-established behavioral definition for the concept. The second is a theoretical study that seeks to understand the concept of self to comprehend self-esteem and proposes a behavioral definition that takes into account the relevant factors in its construction, especially social interactions. The third study investigates the applicability of the Function Acquisition Speed Test (FAST) in measuring self-esteem, comparing the results obtained with those of a Rosenberg Self-Esteem Scale. The results indicate positive self-esteem in participants, both in the FAST and the Rosenberg Self-Esteem Scale, though no correlation was found between the results of the two instruments. Together, these studies contribute to a broader understanding of self-esteem from a behavioral perspective and explore different methods of assessing this psychological construct.